(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the clinical and epidemiological profile of cases of poisoning by pesticides in the State of Piauí between the years 2009 and 2019, through the Notifiable Diseases Information System of the Unified Health System Information Department (SINAN-DATASUS). This is a descriptive research with a quantitative and retrospective approach, of documentary character. The results revealed that, in the period evaluated, 251 cases were recorded, where the year 2017 obtained the highest percentage, with 38 cases (15.2%), which occurred mainly in Teresina, followed by the municipalities of Bom Jesus and Floriano. The profile of these victims was more prominent in the age group of 20 to 39 years with 154 cases (61.35%), being mostly male with 194 cases (77.3%), of brown color with 182 cases (72.5%) and 84 cases (33.47%) presented incomplete elementary education. Most cases were due to suicide attempts with 93 cases (37.1%) followed by accidental cases with 85 cases (33.9%), the most prevalent being acute and single exposures with 172 cases (68.5%), which evolved to healing and without sequelae in 160 cases (63.7%). Therefore, the study also revealed that the number of cases of poisoning by pesticides in Piauí is rising, which can be reversed with greater control in the marketing of pesticides, hindering the access of the population to these substances, in order to avoid cases of poisoning and damage to the health of the population.